Leishmania donovani Lipophosphoglycan Increases Macrophage-Dependent Chemotaxis of CXCR6-Expressing Cells via CXCL16 Induction - Chaparro, Visnu (Infect Immun, 2019)
CXCL16 is a multifunctional chemokine that is highly expressed by macrophages and other immune cells in response to bacterial and viral pathogens; however, little is known regarding the role of CXCL16 during parasitic infections. The protozoan parasite Leishmania donovani is the causative agent of visceral leishmaniasis. Even though chemokine production is a host defense mechanism during infection, subversion of the host chemokine system constitutes a survival strategy adopted by the parasite. Here, we report that L. donovani promastigotes upregulate CXCL16 synthesis and secretion by bone marrow-derived macrophages (BMDM). In contrast to wild-type parasites, a strain deficient in the virulence factor lipophosphoglycan (LPG) failed to induce CXCL16 production. Consistent with this, cell treatment with purified L. donovani LPG augmented CXCL16 expression and secretion. Notably, the ability of BMDM to promote migration of cells expressing CXCR6, the cognate receptor of CXCL16, was augmented upon L. donovani infection in a CXCL16- and LPG-dependent manner. Mechanistically, CXCL16 induction by L. donovani required the activity of AKT and the mechanistic target of rapamycin (mTOR) but was independent of Toll-like receptor signaling. Collectively, these data provide evidence that CXCL16 is part of the inflammatory response elicited by L. donovani LPG in vitro. Further investigation using CXCL16 knockout mice is required to determine whether this chemokine contributes to the pathogenesis of visceral leishmaniasis and to elucidate the underlying molecular mechanisms.